Geographic Survey of Oxyspirura Petrowi Among Wild Northern Bobwhites in the United States - Bradley Kubečka; Andrea Bruno; Dale Rollins (National Quail Symposium Proceedings, 2017)
Eyeworms (Oxyspirura petrowi) are potentially associated with northern bobwhite (Colinus virginianus) declines. We examined hunter-donated bobwhites from the 2013–2015 hunting seasons in 9 states to document infection prevalence (% of bobwhites [of total n]) and intensity (mean no. of eyeworms ± SE). Four states harbored infected bobwhites: Texas (59.1% [n = 110], 15.6 ± 2.1), Oklahoma (52.1% [n = 121], 6.9 ± 1.2), Virginia (14.8% [n = 27], 2.5 ± 1.0), and Alabama (1.6% [n = 61], 2.0). Prevalence and intensity of eyeworms in the Texas Rolling Plains were greater (P < 0.001 and P = 0.002, respectively) than in any other area sampled. Based on our survey, eyeworms are locally prevalent and abundant in bobwhites from the Rolling Plains ecoregion, but virtually nonexistent in many areas that we surveyed.
Keywords: colinus virginianus; northern bobwhite; eyeworm; oxyspirura petrowi; rolling plains